ANALISIS TERHADAP PELAKSANAAN DAN DAMPAK KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SEBAGAI PENERAPAN KURIKULUM MERDEKA DI SDN 01 SUNGAI RUMBAI - Imelda Adima Putri; Zelhendri Zen; Fetri Yeni; Novrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Strengthening Pancasila Student Profile Project (P5) is a project-based co-curricular activity designed to prioritize the achievement of competencies and character development in accordance with the Pancasila Student Profile, which is formulated based on graduate competency standards. This descriptive qualitative study aims to examine the implementation of the P5 Project at SDN 01 Sungai Rumbai, identify the impacts experienced during its execution, and analyze the supporting and inhibiting factors in the project's implementation. The research subjects included the principal, teachers, facilitator team, and students. Data were collected through observations, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that: (1) The P5 Project at SDN 01 Sungai Rumbai was implemented through the "Kutanan Sayuranku" project with the theme of Local Wisdom; (2) The project had positive impacts, such as providing new knowledge to students, fostering a sense of responsibility, and enhancing teamwork skills; (3) Supporting factors included the availability of vacant land provided by the school, active discussions between teachers and facilitators, and enthusiasm from both teachers and students. Inhibiting factors included limited equipment, students frequently forgetting to bring necessary tools, and financial constraints to meet the project’s needs. This study provides insights into the practical implementation of project-based learning within the Merdeka Curriculum framework to strengthen student competencies and